Information redundancy neglect versus overconfidence: A social learning experiment - Marco Angrisani; Antonio Guarino; Philippe Jehiel; Toru Kitagawa (Centre for Microdata Methods and Practice (cemmap), 2018)
We study social learning in a continuous action space experiment. Subjects, acting in sequence, state their belief about the value of a good, after observing their predecessors' statements and a private signal. We compare the behavior in the laboratory with the Perfect Bayesian Equilibrium prediction and the predictions of bounded rationality models of decision making: the redundancy of information neglect model and the overconfidence model. The results of our experiment are in line with the predictions of the overconfidence model and at odds with the others'.
Keywords: 330